THE EFFECT OF SEISMIC ISOLATION SYSTEM TYPE FRICTION PENDULUM SYSTEM (FPS) ON A 12-STOREY APARTMENT HIGHRISE BUILDING IN BANJARMASIN, SOUTH KALIMANTAN - Ramadhani, Muhammad Said; Darmawan, Arya Rizki (Universitas Lambung Mangkurat, 2026)
Indonesia is a region that is prone to earthquake. To minimize the damage done to the structure, one way it to use a Base Isolation. One type of Base Isolation is Friction Pendulum System (FPS). Considering Banjarmasin City is now in an earthquake zone, the implementation of FPS can reduce the damage done to the structure with the usage of FPS. Therefore this research will discuss the behavior of structures by comparing fixed-base with friction pendulum system. The research adheres to SNI 1726:2019, SNI 1727:2020, dan SNI 2847:2019 to facilitate the analysis the research utilize SAP2000 program. The research utilizes concrete with a compressive strength of 30 MPa and rebars with yield strengths of 420 MPa and 280 MPa. It’s revealead that the base shear remained nearly identical between the fixed-base and FPS-isolated structures, with the FPS structure experiencing a slight increase (0.05%). Additionally, the use of FPS amplified interstory drift by up to 53%, while offering a beneficial reduction of up to 38% in beam internal forces. Keywords: Base Isolation, Friction Pendulum System, SRPMK, Fixed Base, Vibration Period, Displacement, Base Shear, Deflection